New Jacobian Matrix and Equations of Motion for a 6 DOF Cable-driven Robot - Ali Afshari (International Journal of Advanced Robotic Systems, 2008)
In this paper, we introduce a new method and new motion variables to study kinematics and dynamics of a 6 d.o.f cabledriven robot. Using these new variables and Lagrange equations, we achieve new equations of motion which are different in appearance and several aspects from conventional equations usually used to study 6 d.o.f cable robots. Then, we introduce a new Jacobian matrix which expresses kinematical relations of the robot via a new approach and is basically different from the conventional Jacobian matrix. One of the important characteristics of the new method is computational efficiency in comparison with the conventional method. It is demonstrated that using the new method instead of the conventional one, significantly reduces the computation time required to determine workspace of the robot as well as the time required to solve the equations of motion.